FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN UNTUK MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI (Studi Kasus Pada KPP Pratama Pekalongan) - Fathurrohman, 09.05.52.0131; Badjuri, Achmad (Students Journal of Accounting and Banking, 2013)
The pupose aim detects cognizance influence character pays tax, erudition and comprehension about tax regulation, good perception on efektifitas taxation system, taxpayer obedience and taxation sanction. Population in this watchfulness individual person taxpayer at kpp pratama pekalongan. while sample in this watchfulness 107 taxpayer. data that used in this watchfulness primary data passes kuesioner and secondary data that is data that is got based on datas that available, in this case watchfulness datas are got from data about profile kpp pratama pekalongan, individual person taxpayer. analyzer that used in this watchfulness doubled linear regression. The result shows that found influence significant positive between cognizance pays tax towards will pay tax. found influence significant positive between erudition and taxation regulation comprehension towards will pays tax. found influence significant positive between good perception on taxation system effectiveness good towards will pays tax. found influence significant positive between taxpayer obedience towards will pays tax. found influence significant positive between taxation sanction towards will pays tax. found influence significant between taxation cognizance, erudition and taxation regulation comprehension, good perception on good taxation system effectiveness, taxpayer obedience and taxation sanction according to together towards will pays tax Keywords: taxation cognizance, erudition and taxation regulation comprehension, good perception on good taxation system effectiveness, taxpayer obedience, will taxation sanction pays tax